Enantioselective Nazarov Cyclizations Catalyzed by an Axial Chiral C6F5‐Substituted Boron Lewis Acid. Issue 35 (26th July 2018) - Süsse, Lars; Vogler, Maria; Mewald, Marius; Kemper, Benedict; Irran, Elisabeth; Oestreich, Martin
Abstract: A chiral variant of B(C6 F5 )3 with a 3, 3′‐disubstituted binaphthyl backbone is shown to catalyze Nazarov cyclizations with high levels of enantio‐ and diastereocontrol. The parent B(C6 F5 )3 also promotes these ring closures efficiently. This electrocyclization is another example of the still small family of C−C bond formations mediated by B(C6 F5 )3 as the catalyst. Abstract : Boron with torque ! A chiral variant of tris(pentafluorophenyl)borane [B(C6 F5 )3 ] promotes Lewis acid catalyzed Nazarov cyclizations of activated precursors with high enantiomeric excesses. The diastereoselectivity is also good, usually favoring the cis isomer in synthetically useful ratios. B(C6 F5 )3 catalyzes the ring closure of the same set of substrates in racemic fashion.